Loob: Indigeneous, prosocial, and normative rationality in a dictator game - Largoza, Gerardo L. (Animo Repository, 2007)
This work offers a modest two part contribution to the ongoing project to social homo economics. Part 1 argues that Alejo (1990) phenomenological reflections on loob, a Filipino term for personhood, are compatible with the emerging literature on neuroeconomics and amenable to empirical investigation. Part 2 tests specific claims about loob in a dictator game experiment conducted among 480 low income trilingual students in a rural municipality in Camarines Sur. The unusually high incidence of hyper fair offers seems consistent with a self other conception of personhood albeit one that does not appear sensitive to priming. A robust language effect was also found when instructions were coded in English as opposed to Tagalog and Bikol, but one that worked in unexpected ways.